Impact of Nigrospora oryzae_Derived Natural Products on Photosynthesis and Oxidative Stress in Eichhornia crassipes - Chamroon Laosinwattana; Nutcha Manichart; Pattharin Wichittrakarn; Kaori Yoneyama; Montinee Teerarak; Hataichanok Passara (My University, 2025)
Abstract Interest in natural herbicides has been growing due to government policies restricting synthetic herbicide use in many countries. In that regard, this study investigates the potential of Nigrospora oryzae extract as a natural herbicide against the aquatic invasive weed Eichhornia crassipes . A stable formulation was developed with a droplet size of 36.44 ± 0.36 nm and a zeta potential of ‐62.59 mV. Pot‐based experiments revealed the N. oryzae extract induced 38.33% phytotoxicity within 24 hours, increasing to 84.72% by 28 days post‐treatment. Scanning electron microscopy demonstrated morphoanatomical changes in epidermal tissue and stroma of E. crassipes , such as erosion of epicuticular waxes and degeneration of epidermis cells. The treatment significantly reduced the photosynthetic pigment content while increasing hydrogen peroxide (46.26%), malondialdehyde (17.49%), and proline (19.16%) levels, causing cellular electrolyte leakage. Activities of superoxide dismutase, catalase, ascorbate peroxidase, and guaiacol peroxidase were significantly elevated ( p <0.05), indicating oxidative damage. These findings demonstrate that N. oryzae extract can disrupt growth and photosynthesis and induce oxidative stress in E. crassipes , suggesting its potential as a source of natural herbicide for industrial application.
Keywords: Eichhornia crassipes; Biological Control of Invasive Species